Application of the Radec Model with an Ethnoscience Insight for the Analysis of Seasonal Change in Lampung - Ida Fiteriani; Wahyu Sopandi; Wahyudin Wahyudin; Asep Herry Hernawan; Baharudin Baharudin (Jurnal Pemberdayaan Masyarakat, 2026)
This study explores the analytical thinking skills of prospective Madrasah Ibtidaiyah (MI) teacher students in understanding seasonal changes in Lampung through the ethnoscience-based RADEC learning model integrated with the local Ngumbai Sabah tradition. The aim is to bridge scientific concepts with local wisdom through both verbal and visual representations.The research employed a quantitative experimental design with a One-Pretest–Posttest design. The sample consisted of PGMI students from Class H, and the instrument was an open-ended essay test assessing students’ abilities to differentiate, organize, connect concepts, and present them visually. Data were analyzed descriptively and inferentially, including a paired-sample t-test to evaluate the effectiveness of RADEC.Results show that the ethnoscience-based RADEC model effectively improves students’ ability to differentiate and organize concepts. However, their ability to connect concepts comprehensively remains limited, especially in visual representations. The main hindering factors are misconceptions regarding basic science concepts, particularly seasonal change phenomena, and difficulties in representing the relationships between scientific concepts and Lampung’s local wisdom. Most visual outputs remain descriptive and fragmented, highlighting the need to strengthen higher-order analytical thinking skills and visual literacy.